Atrial high-rate episodes intensify R2CHA2DS2-VASc score for prognostic stratification in pacemaker patients - Yi-Pan Li; Ju-Yi Chen; Tse-Wei Chen; Wei-Da Lu (Scientific Reports, 2023)
Abstract Patients with device detected atrial high-rate episodes (AHRE) have an increased risk of MACE. The R2CHA2DS2-VASc, CHADS2, R2CHADS2 and CHA2DS2-VASc score have been investigated for predicting major adverse cardiovascular events (MACE) in different groups of patients. We aimed to evaluate the R2CHA2DS2-VASc score in combination with AHRE ≥ 6 min for predicting MACE in patients with dual-chamber PPM but no prior atrial fibrillation (AF). We retrospectively enrolled 376 consecutive patients undergoing dual-chamber PPM implantation and no prior AF. The primary endpoint was subsequent MACE. For all patients in the cohort, CHADS2, R2CHADS2, CHA2DS2-VASc, R2CHA2DS2-VASc scores and AHRE ≥ or < 6 min were determined. AHRE was recorded as a heart rate > 175 bpm (Medtronic) or > 200 bpm (Biotronik) lasting ≥ 30 s. Multivariate Cox regression analysis with time-dependent covariates was used to determine the independent predictors of MACE. ROC-AUC analysis was performed for CHADS2, R2CHADS2, CHA2DS2-VASc, and R2CHA2DS2-VASc scores and then adding AHRE ≥ 6 min to the four scores. The median age was 77 years, and 107 patients (28.5%) developed AHRE ≥ 6 min. After a median follow-up of 32 months, 46 (12.2%) MACE occurred. Multivariate Cox regression analysis showed that R2CHA2DS2-VASc score (HR, 1.485; 95% CI, 1.212–1.818; p < 0.001) and AHRE ≥ 6 min (HR, 2.125; 95% CI, 1.162–3.887; p = 0.014) were independent predictors for MACE. The optimal R2CHA2DS2-VASc score cutoff value was 4.5 (set at ≥ 5), with the highest Youden index (AUC, 0.770; 95% CI, 0.709–0.831; p < 0.001). ROC-AUC analysis of the four risk scores separately combined with AHRE ≥ 6 min all showed better discriminatory power than the four scores alone (All Z-statistic p < 0.05). In patients with PPM who develop AHRE ≥ 6 min, it is crucial to perform risk assessment with either four scores to further stratify risk for MACE.